DYSTOCIA DUE TO CONJOINED TWIN MONSTER IN A COW - KUMAR, S; PANDEY, A K; KUSHWAHA, R B; SHARMA, U; DWIVEDl, D K (The Indian Journal of Animal Reproduction, 2023)
This paper reports a rare case of dystocia due to conjoined twin monster in a cow.
Keywords: Conjoined twin monster; Dystocia,; Cow.